PENGARUH KUALITAS PELAYANAN TERHADAP WORD OF MOUTH YANG DIMEDIASI OLEH KEPERCAYAAN PELANGGAN PADA PT. AUTO BAGUS RENT A CAR DENPASAR - Indriani, Anak Agung Sagung Istri; Nurcaya, I Nyoman (E-Jurnal Manajemen, 2015)
This study aims to find out how to manage the quality of service to build (word of mouth) WOM customers mediated by the trust of customers. This research was conducted at PT. Good Auto Rent A Car Denpasar. Samples taken a total of 110 respondents with pusposive sampling method. The data collection questionnaires using 5-point Likert scale, to measure the 11 indicators. The analysis technique used is the path analysis. These results indicate that the quality of service significant positive effect on word of mouth (WOM), quality of service significant positive effect on customer trust, customer trust positive significant effect on WOM, and trust significantly mediate the quality of service to the (word of mouth ) WOM.
Keywords: word of mouth; kepercayaan; kualitas pelayanan